Isokinetic knee strength qualities as predictors of jumping performance in high-level volleyball athletes: multiple regression approach - Sattler, T.; Sekulic, D.; Spasic, M.; Osmankac, N.; Vicente Joao, P.; Dervisevic, E.; Hadzic, V. (The Journal of Sports Medicine and Physical Fitness, 2016)
ABSTRACT: Previous investigations noted potential importance of isokinetic strength in rapid muscular performances, such as jumping. This study aimed to identify the influence of isokinetic--knee--strength on specific jumping performance in volleyball. The secondary aim of the study was to evaluate reliability and validity of the two volleyball--specific jumping tests. The sample comprised 67 female (21.96±3.79 years; 68.26±8.52 kg; 174.43±6.85 cm) and 99 male (23.62±5.27 years; 84.83±10.37 kg; 189.01±7.21 cm) high--volleyball players who competed in 1st and 2nd National Division. Subjects were randomly divided into validation (n = 55 and 33 for males and females, respectively) and cross--validation subsamples (n = 54 and 34 for males and females, respectively). Set of predictors included isokinetic tests, to evaluate the eccentric and concentric strength capacities of the knee extensors, and flexors for dominant and non--dominant leg. The main outcome measure for the isokinetic testing was peak torque (PT) which was later normalized for body mass and expressed as PT/Kg. Block--jump and spike--jump performances were measured over three trials, and observed as criteria. Forward stepwise multiple regressions were calculated for validation subsamples and then cross--validated. Cross validation included correlations between and t--test differences between observed and predicted scores; and Bland Altman graphics. Jumping tests were found to be reliable (spike jump: ICC of 0.79 and 0.86; block--jump: ICC of 0.86 and 0.90; for males and females, respectively), and their validity was confirmed by significant t--test differences between 1st vs. 2nd division players. Isokinetic variables were found to be significant predictors of jumping performance in females, but not among males. In females, the isokinetic--knee measures were shown to be stronger and more valid predictors of the block--jump (42% and 64% of the explained variance for validation and cross--validation subsample, respectively) than that of the spike--jump (39% and 34% of the explained variance for validation and cross--validation subsample, respectively). Differences between prediction models calculated for males and females are mostly explained by gender--specific biomechanics of jumping. Study defined importance of knee--isokinetic--strength in volleyball jumping performance in female athletes. Further studies should evaluate association between ankle--isokinetic--strength and volleyball--specific jumping performances. Results reinforce the need for the cross--validation of the prediction--models in sport and exercise sciences.